Kitabah K.H Husein Muhammad Tentang Kesetaraan Gender - Amaliyah, Dewi; Wahyudin, Aep; Risdayah, Enok (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2023)
This research aims to determine the concept and perspective of Husein Muhammad’s book on gender equality in the Islamic Book, Women-Friendly Religion and the views of gender equality according to Husein Muhammad. The research method used is a qualitative descriptive method with a feminist approach. This research uses library research or library study of main research data. The results of this research show that in the struggle for gender equality, Husein Muhammad’s thinking is based on anti-patriarchal monotheism, which means no glorification of other creatures except the Creator. He also started from thinking in terms of respect for human rights (HAM). The thing that is the basis of human rights is also the core of Islamic teachings itself, namely equality. Equality confirms that the position of humans (women and men) as God’s creatures is the same before Him